Novel TRAF1‐ALK fusion identified by deep RNA sequencing of anaplastic large cell lymphoma. Issue 11 (2nd September 2013) - Feldman, Andrew L.; Vasmatzis, George; Asmann, Yan W.; Davila, Jaime; Middha, Sumit; Eckloff, Bruce W.; Johnson, Sarah H.; Porcher, Julie C.; Ansell, Stephen M.; Caride, Ariel
<x xml:space="preserve">Abstract</x> Chromosomal translocations leading to expression of abnormal fusion proteins play a major role in the pathogenesis of various hematologic malignancies. The recent development of high‐throughput, "deep" sequencing has allowed discovery of novel translocations leading to a rapid increase in understanding these diseases. Translocations involving the anaplastic lymphoma kinase (ALK) gene leading to ALK fusion proteins originally were discovered in anaplastic large cell lymphomas (ALCLs). Among ALCLs, NPM1‐ALK fusions are most common and lead to nuclear localization of the fusion protein. Here, we present a 50‐year‐old male with ALCL demonstrating cytoplasmic ALK immunoreactivity only, suggesting the presence of a non‐NPM1 fusion partner. We performed deep RNA sequencing of tumor tissue from this patient and identified a novel transcript fusing Exon 6 of TRAF1 to Exon 20 of ALK. The TRAF1‐ALK fusion transcript was confirmed at the mRNA level by Sanger sequencing and the fusion protein was visualized by Western blot. The discovery of this TRAF1‐ALK fusion expands the diversity of known ALK fusion partners and highlights the power of deep sequencing for fusion transcript discovery. © 2013 Wiley Periodicals, Inc.